1999
DOI: 10.1902/jop.1999.70.8.823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogen and Osteopenia/Osteoporosis on Clinical Periodontitis in Postmenopausal Women

Abstract: These data suggest that E2 supplementation (serum E2>40 pg/ml) is associated with reduced gingival inflammation and a reduced frequency of clinical attachment loss in osteopenic/osteoporotic women in early menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
2
11

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(162 citation statements)
references
References 20 publications
3
146
2
11
Order By: Relevance
“…It was concluded that estrogen supplementation may lower gingival inflammation and rate of clinical attachment loss in osteopenic/osteoporotic population. 39 Weyant et al studied a cross-section of a large sample of osteoporotic women in the postmenopausal age. The average age of participants was 70.7 years and BMD was measured using single photon absorptiometry at the hip, spine, radius and calcaneus regions.…”
Section: Calcitoninmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that estrogen supplementation may lower gingival inflammation and rate of clinical attachment loss in osteopenic/osteoporotic population. 39 Weyant et al studied a cross-section of a large sample of osteoporotic women in the postmenopausal age. The average age of participants was 70.7 years and BMD was measured using single photon absorptiometry at the hip, spine, radius and calcaneus regions.…”
Section: Calcitoninmentioning
confidence: 99%
“…49 Again, a study by Richard A etal concluded that estrogen supplementation may lower gingival inflammation and rate of clinical attachment loss in osteopenic/osteoporotic population. 39 Future research: Currently marketed osteoporosis therapies including bisphosphonates and selective estrogen modulators are efficacious but inconvenient for the patients because of the need for frequent administration and the risk of adverse effects. The active immunization strategy against TRANCE/RANKL using C-TRANCE-VLPs may offer a safe, efficient and cost-effective new therapeutic option for the treatment of osteoporosis.…”
Section: Mechanismmentioning
confidence: 99%
“…A number of studies have suggested that the risk of postmenopausal tooth loss is reduced by oestrogen replacement (43). Furthermore, lower oestrogen levels have been linked to gingival inflammation (44) and reduced clinical attachment levels (45).…”
Section: Sex Steroid Hormonesmentioning
confidence: 99%
“…No entanto, analisando os grupos de mulheres estrógeno suficientes e deficientes, os parâmetros periodontais não mostraram tal associação, como apresentado em estudos semelhantes 13,16,21 . Estes estudos concluíram que a osteopenia na pós-menopausa constitui fator de risco para a doença periodontal.…”
Section: Densitometria óSsea Mineralunclassified